Distributed innovation processes: Key concepts, case studies, current developments - Jan-Felix Schrape (Universität Stuttgart, Institut für Sozialwissenschaften, Abteilung für Organisations- und Innovationssoziologie, 2024)
This paper provides a brief overview of the concepts of collective invention, user innovation, and open innovation. All three terms describe variants of distributed innovation processes and can be linked to further ideas of socio-economic decentralization. First, the conceptual differences between collective invention, user innovation, and open innovation are elaborated. Second, exemplary case studies from the past decades are presented before more recent forms of distributed innovation in the development of information technologies are discussed. In this context, it becomes evident that distributed innovation processes and internal research and development activities in public and private sector organizations are not in competition with each other but rather in a complementary relationship. – – Das vorliegende Diskussionspapier bietet einen kompakten Überblick über die Konzepte der Collective Invention, User Innovation und Open Innovation, die unterschiedliche Ausprägungen verteilter Innovationsprozesse beschreiben. Nach einer Aufarbeitung ihrer jeweiligen konzeptuellen Schwerpunkte wird ihr praktisches Zusammenspiel anhand exemplarischer Fallstudien aus den letzten Jahrzehnten illustriert. Daran anknüpfend erfolgt die Diskussion neuerer Entwicklungen auf dem Feld der Informationstechnologien sowie eine kritische Würdigung. Dabei wird ersichtlich, dass verteilte Innovationsprozesse und interne Forschungs- und Entwicklungsaktivitäten in öffentlichen und privatwirtschaftlichen Organisationen in der Regel nicht in einem konkurrierenden, sondern in einem komplementären Verhältnis zueinander stehen.
Keywords: 300; Open Innovation; Kundenintegration; Geschichte